ABC: AI, Blockchain, and Cybersecurity for healthcare new innovations for the post-quantum era - Metcalf, David; Hadley, Dexter; Hooper, Max; Pappas, Harry; Dhillon, Vikram (Intelligent health series, 2024)
Join us in the beginning of a conversation and what we hope will be a community dedicated to leveraging some of the latest technologies for a next generation of infrastructure. After decades of building enterprise systems, a fundamental change is occurring because of AI, Blockchain, and next-generation Cybersecurity (ABC). This is poised to affect many industries and areas of society, not least of which is healthcare. We are excited to join like-minded colleagues who have agreed to share their expertise and examples in the early days of integrating these technologies into a unified architecture that can meet operational goals. In the case of healthcare, can artificial intelligence, blockchain, and cybersecurity technologies lead to better, faster, and cheaper healthcare and ease the burden on healthcare providers? This may extend to the whole health ecosystem, not just providers and the hospitals and systems, but also to the insurers and payers, and of course the patients or health consumers interested in wellness and well-being. Benefits to healthcare research, drug discovery, and next generation genomic and novel health discoveries could accelerate discovery, trial, and wider knowledge and adoption of novel tools and techniques. In this book, we will explore the potential synergies and benefits of ABC with particular interest in the way that they can make up for weaknesses and be used appropriately and with proper cautions given the potential power of AI. Blockchain for verification, privacy and trust, along with good cybersecurity practices, often called cyber hygiene -- especially with the potential for new and novel attacks far beyond ransomware as the age of quantum computing accelerates. We hope you will enjoy exploring the breadth of knowledge and expertise represented by the many contributors and early insights and case studies.